The application of terrestrial laser scanning and web-based geographical information system for indoor asset management - Lee, Szue Yann (2015)
In this era of information technology, majority of organizations have started using information system to record and store information for the existing assets for more effective asset management. However, there are some organizations are still practicing the manual filing system to keep the records. Geographic Information System had been introduced to the asset management. Recently, the Geographical Information System based on three-dimensional technology and internet environment are one of the emerging issues in Geographical Information System field. Thus, this research attempts to improve the weaknesses of the current asset management practice by developing a web-based asset information management system with map visualization and spatial information. Leica Scan Station C10 was used to capture three-dimensional indoor asset models to support the spatial data and store the attribute data of assets into a Geographical Information System database. Several software are used in this study which included Autodesk Revit Architecture, Trimble SketchUp, XAMPP, phpMyAdmin, Netbeans IDE and VRML viewer. The asset management system enables users to manage asset information and database. An added-value designed in the system has enabled spatially query regarding asset information and retrieve asset location through three-dimensional model. This system was designed and developed based on the user requirements. The system performance had been tested by end-users and experts in related field. The results of user testing had proved the developed system is helpful for managing indoor assets. The computerized asset management system enables asset records store in an organized database system. Lastly, new feature of integrating map and three dimensional viewing in the asset management system can benefits in analysis with Geographic Information System concept such as doing location query, zoom-in and zoom-out, as well as visualize asset location from three-dimension map.